A Novel Multi-Attribute Authority Based Encryption for Controlling Access to Cloud Data - musluh, Saif Khalid; Nuiaa, Riyadh Rahef (Journal of College of Education, 2021)
Cloud computing has changed the way IT department are working with respect to outsourcing data and having controlled access to the data. In the new computing paradigm that supports on-demand services, the storage service became an attractive service for many cloud users. When data is outsourced to cloud, there is an issue of giving controlled access to the cloud data. Many schemes came into existence. Some of the schemes focus on auditing, provable data possession and proof of irretrievability. Some other schemes threw light into the access control on the cloud data. While giving privileges to accessing data attribute based encryption has achieved significant fine-grained control over the data. In this paper we propose a methodology that can allow controlled access to cloud data with multi-attribute authority based encryption. The multi-attribute based approach is used to make the scheme robust. Moreover the proposed approach is aimed at prevention of identity leakage and also achieves anonymity as well. We built a prototype application that demonstrates the proof of concept. The empirical results revealed that the proposed method improves access control significantly.